Evaluation of bioprocessed soybean meal as a protein ingredient in extruded dog and cat diets - Chen, Youhan (My University, 2025)
The utilization of traditional soybean meal in pet food has been limited by its low methionine content and flatulence-causing oligosaccharides. Microbially enhanced soybean protein (MEP) and Aspergillus oryzae fermented soybean meal (F-SBM) are bioprocessed soybean meal products with improved nutritional value. The objectives of this thesis were to determine: 1) the optimal inclusion level of MEP for extruded pet food to enhance nutrient utilization and palatability, 2) the optimal A. oryzae fermentation process to improve soybean meal protein composition, and 3) the performance of F-SBM compared to traditional soybean protein products in extruded dog food. The effects of MEP and F-SBM on extrusion processing, kibble characteristics, palatability, nutrient digestibility, and stool quality were assessed in dogs and cats. The first experiment evaluated dog and cat diets with increasing levels of MEP (0, 5, 10, and 15% substitution for soybean meal). The second experiment optimized inoculation dosage and fermentation duration to enhance protein content in soybean meal and compared a diet with 30% F-SBM to diets with either 30% traditional soybean meal (SBM), 30% traditional soybean meal and 1% Amaferm (AMF), or 18% soybean protein isolate (SPI). Diets were fed to 12 dogs or 12 cats in a 4x4 replicated Latin square design, with a 9-day adaptation period followed by a 5-day total fecal collection. Data were analyzed using a generalized linear mixed model (GLIMMIX, SAS version 9.4, SAS Institute, Inc., Cary, NC) with treatment as a fixed effect and animal and period as random effects. In the first study, the replacement of traditional soybean meal with MEP increased (P＜0.05) kibble expansion in both dog and cat foods. Fecal dry matter output decreased (P＜0.05) in a linear manner as MEP increased in dog diets. Fecal quality in cats were not affected by MEP inclusion. Overall, nutrient digestibility was maintained with increased levels of MEP. Fecal ammonia showed a linear increase (P＜0.05) as MEP increased in cat diets. For palatability, dogs preferred (P < 0.05) diet with 15% soybean meal to diets with 5 or 10% MEP, while cats preferred (P < 0.05) diet with 10% MEP to a diet with 15% soybean meal. For the second experiment, an Aspergillus oryzae spore inoculation dosage of 1×10⁴ spores/g and fermentation duration of 36 hours were found to be optimal for increasing protein content and avoiding increasing soluble dietary fiber in the soybean meal. The F-SBM had improved (P < 0.05) nutrient profile and increased (P < 0.05) specific mechanical energy and kibble expansion compared to traditional soybean meal during extrusion. Fermentation also decreased (P < 0.05) content of sucrose and oligosaccharides in soybean meal. Fecal quality and nutrient digestibility were similar among dogs fed on the SBM, the FSBM and the AMF, while those of dogs on SPI had less (P < 0.05) fecal output and greater (P < 0.05) nutrient digestibility. Colonic fermentation was the greatest (P < 0.05) in dogs on the AMF and the least (P < 0.05) in dogs on SPI, with dogs on SBM and FSBM intermediate. Dogs preferred SBM to FSBM but did not show preference between SBM and SPI. Overall, the bioprocessed soybean meals did not affect fecal quality, general nutrient digestibility when fed to cats and dogs compared to diets with traditional soybean meal. To maintain palatability, the inclusion level should not exceed 15% of the diet. Further research is needed to explore health benefits and more processing characteristics of bioprocessed soybean meal as a protein source in pet foods.
Keywords: Fermentation; Soybean protein; Dogs; Cats; Extrusion; Digestibility